Glycine betaine in plant responses and tolerance to abiotic stresses - Afsana Jarin; Uttam Kumar Ghosh; Md. Saddam Hossain; Apple Mahmud; Md. Arifur Rahman Khan (Discover Agriculture)
Abstract Abiotic stresses pose a significant challenge to sustainable crop production in our ever-changing global environment. These stresses have an impact on plant growth, development, and production through various mechanisms, including morpho-physiological, biochemical, and molecular changes, as well as interactions with secondary metabolites. Glycine betaine (GB) emerges as a critical compatible solute in plant, playing a key role in maintaining the morpho-physiological and biochemical processes within the plant. Plant species have different abilities to produce GB, the amount of GB accumulated in plants is closely connected to their capacity to withstand various types of abiotic stresses. Application of exogenous GB or genetic engineering-induced biosynthesis of GB has been demonstrated to enhance tolerance under abiotic stresses. Additionally, plants with accumulated GB show increased in flowers and seed production, when grown under normal conditions. GB helps plants cope with abiotic stresses by regulating stress hormones, plant growth hormones, reactive oxygen species detoxifying molecules, and ion homeostasis pathways, thereby enhancing the plant's ability to survive under challenging conditions. This comprehensive review aims to offer updated insights into GB metabolism and synthesis in plants in response to abiotic stresses. It explores the morpho-physiological, biochemical, and molecular factors associated with GB's role in mitigating the impact on the structure and functionality of photosystem II (PSII). Furthermore, this review examines GB's modulation of chaperone functions within plant cells, preventing misfolded protein formation and safeguarding crucial complexes like PSII from structural damage, as well as its interaction with other molecules whose functions are impaired during abiotic stress conditions.